S76 Increased risk of cardiovascular disease in asthma. (11th November 2022) - Valencia-Hernandez, CA; Zakeri, R; Sundaram, V; Bloom, CI
Abstract : Introduction and Objectives: Several studies have found asthma to be associated with an increased risk of cardiovascular disease (CVD) and mortality. Underlying mechanisms may be related to shared risk factors including smoking and chronic inflammation. However, findings are not consistent and studies to date have been limited by sample size and bias, including unmeasured confounding and recall bias. This study explores the association between asthma and CVD in a large nationally representative cohort of patients in England, using electronic healthcare records (EHR). Methods: A cohort of adult asthma patients, January 2004 to January 2019, were matched 1:1 to the general population by gender and age, using primary care EHR (Clinical Practice Research Datalink) linked to hospital records (Hospital Episode Statistics) and mortality data (Office for National Statistics). Cardiovascular events were defined as a composite of hospitalisations and mortality due to myocardial infarction, tachyarrhythmia, ischaemic cerebrovascular events and heart failure. Cox-proportional-hazards models were fit adjusting for sociodemographic characteristics, body composition measures, health behaviours and comorbidities. Results: The cohort included 1, 265, 900 individuals (56% female) with a mean age of 34 years (SD=13.8) and median follow-up of 4.2 years (IQR 1.7–9.9). Compared with the general population at baseline, there was a higher proportion in the asthma patients of atopy (43.3% vs. 19.9%), obesity (18.5% vs. 11.2%), smoking, (28.8% vs. 25.7%), obstructive sleep apnoea (0.2% vs 0.1%), diabetes (2.3% vs 1.8%) and hyperlipidaemia (3.1% vs 2.3%). The number of composite events was higher in asthma patients than the general population (rates per 1, 000 person years: asthma = 1.63, 95% CI 1.59–1.66, general population = 2.00, 95% CI 1.96–2.05). Patients with asthma had an 18% higher risk of an incident CVD event compared to the general population, adjusted hazard ratio 1.18, 95% CI 1.12–1.25 (see table 1 ). Conclusions: In a large nationally representative cohort, asthma was found to be significantly associated with an increased risk of cardiovascular disease as compared to the general population, even after adjusting for major known risk factors.